2019
DOI: 10.3389/fgene.2018.00733
|View full text |Cite|
|
Sign up to set email alerts
|

Functional Urate-Associated Genetic Variants Influence Expression of lincRNAs LINC01229 and MAFTRR

Abstract: Genetic variation in the genomic regulatory landscape likely plays a crucial role in the pathology of disease. Non-coding variants associated with disease can influence the expression of long intergenic non-coding RNAs (lincRNAs), which in turn function in the control of protein-coding gene expression. Here, we investigate the function of two independent serum urate-associated signals (SUA1 and SUA2) in close proximity to lincRNAs and an enhancer that reside ∼60 kb and ∼300 kb upstream of MAF, respectively. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…For 16 loci ( ABCG2, B4GALT1, BCAS3, FGF5, BICC1, HFN4G, IGF1R, INHBB, NFAT5, PDZK1, QRICH2, SLC16A9, SLC17A1, TMEM171, TRIM46, UBE2Q2 ) the pattern of association was consistent between the East Asian and European GWAS suggesting strong similarity between the underlying haplotypic structure and casual variant(s) (Figure S5). The MAF locus contains two association signals in the East Asian population, one that is shared with the European population and one that is specific to the East Asian population (Figure S6) [12]. The lead SNP for the East Asian population is rs889472 ; this variant is common in both European (C-allele = 0.38) and East Asian (C-allele = 0.60) individuals from the 1000 Genomes Project yet there is no serum urate association signal in the European population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 16 loci ( ABCG2, B4GALT1, BCAS3, FGF5, BICC1, HFN4G, IGF1R, INHBB, NFAT5, PDZK1, QRICH2, SLC16A9, SLC17A1, TMEM171, TRIM46, UBE2Q2 ) the pattern of association was consistent between the East Asian and European GWAS suggesting strong similarity between the underlying haplotypic structure and casual variant(s) (Figure S5). The MAF locus contains two association signals in the East Asian population, one that is shared with the European population and one that is specific to the East Asian population (Figure S6) [12]. The lead SNP for the East Asian population is rs889472 ; this variant is common in both European (C-allele = 0.38) and East Asian (C-allele = 0.60) individuals from the 1000 Genomes Project yet there is no serum urate association signal in the European population.…”
Section: Resultsmentioning
confidence: 99%
“…Also, at SLC16A9 there was a second cis -eQTL over CCDC6 that was weakly associated with serum urate levels. Differential cis- and trans -eQTL signals are reminiscent of the situation at the serum urate-associated cis- and trans -eQTL signals at the MAFTRR locus [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the other top hits, five are close to transcription factors involved in kidney and liver development (HNF4G, HNF1A, HNF4A, HLF and MAF). These are not part of a globally enriched gene set, but recent functional work has shown that the associated missense variant in HNF4A results in differential regulation of the urate solute carrier ABCG2 [17], while the MAF association has been shown to regulate SLC5A8 [20]. Finally, two other loci show large signals: a missense variant in INHBC, a TGF-family hormone, and a variant in/near GCKR, a glucose-enzyme regulator.…”
Section: Genetics Of Serum Urate Levelsmentioning
confidence: 99%
“…How rs10011796 (or more likely a variant in linkage disequilibrium) could synergise with rs2231142 to amplify the risk of gout is unclear. However it has previously been reported that a urate-associated variant at the MAF locus influences the expression of MAF via a long non-coding RNA (50). It is possible that in Western Polynesian people with HU, the combination of the 141K risk allele with the rs10011796 CC-genotype has an epistatic effect where an altered amount of 141K is internalized, disrupting important stoichiometric relationships and promoting gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%